EVALUASI EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL DALAM PROSEDUR HIBAH PADA SATUAN KERJA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Djakaria, Nazlia; Ilat, Ventje; Gerungai, Natalia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Internal Control System is a system of business or social system that the company consists of organizational structure, methods and measures to maintain and direct the way the company to move in accordance with corporate goals and programs. The internal control system is used to control all activities undertaken by the company including the grant procedure. The purpose of this study is to evaluate the effectiveness of the internal control system of grant procedures in the Regional Office of the Ministry of Religion Affairs of North Sulawesi Province. In this study the type of data used is qualitative data, while for data sources using primary data and secondary data, and the method of analysis used is descriptive analysis method. Based on the results of the research, it is concluded that the grant procedure in the Regional Office of the Ministry of Religion Affairs of North Sulawesi Province has been effective because it has fulfilled the existing components of internal control.Keywords: Internal Control, Grant Procedures